Case report: Rare heterozygous variant in the NR5A1 gene causing 46,XY complete gonadal dysgenesis with a non-communicating rudimentary uterus - Sasaki, Toru; Suzuki, Shinji; Ono, Masanori; Yamamoto, Akiko; Bingo, Masato; Yamanaka, Gaku; Kuroda, Masahiko; Inagaki, Natsuko; Nishi, Hirotaka (Frontiers in Medicine, 2024)
The nuclear receptor subfamily 5 group A member 1 (NR5A1) gene encodes NR5A1, also known as steroidogenic factor 1, a crucial transcriptional factor regulating adrenal and gonadal development and function. Although pathogenic variants in NR5A1 are known to cause a spectrum of disorders of sex development (DSD), individuals with 46,XY DSD with fully female internal and external genitalia are relatively rare. Herein, we present the case of a patient with 46,XY complete gonadal dysgenesis (CGD) who had a non-communicating rudimentary uterus due to a c.132_134del (p.Asn44del) heterozygous in-frame-deletion in NR5A1 that was diagnosed while treating a pelvic mass in which gynecological malignancy could not be disregarded. Unlike two previous cases with the p.Asn44del variant, this case presented with CGD, a severe DSD phenotype, and we found that the oligogenic inheritance of DSD-causative genes such as SRY, DHX37, SLC26A8, and CFTR may have affected the severity of the clinical phenotype.